PRODUCTION OF 11 C-METHIONINE BY CYCLOTRON AVF JAERI - Sri Hastini (Universitas Gadjah Mada, 2002)
At the Takasaki-site of JAERI, an AVF cyclotron has been constructed for advanced radiation technology research. The cyclotron produces extracted beams particularly light and heavy ions of proton as well as deutron. Target chamber is available for production of 11CO2 a positron emitter radioisotope, by bombardment of proton from nitrogen gas as a target, by 14 N (p,a) 11C reaction. The use of incident energy on target was estimated to be 11 MeV for primary proton energy of 20 MeV and the beam current was 0,1 m A and the irradiation time was 10 minutes for production of 11CO2 and the yield was about 30 MBq (EOB)and for irradiation time 15 minutes and the beam current was 1 mA for production of 11C-Methionine, the yield was about 70 MBq (EOB). Remotely operated automatic and semiautomatic processing systems are used for the production of the 11 C-Methionine agent and the radiochemical purity of the product obtained was determined by High Performance Liquid Chromatography (HPLC) with cation exchange column was LC 10 AD MERCK LICHROSPHER 100 RP-18 and the mobile phase was 10 mM ammonium phormmate, the mean of retention time was 1,815 minutes and the radiochemical purity to be more than 90 %. The product was used for plant studies and visualized by PETIS (Positron Emission Tracer Imaging System)